TSH Variability of Patients Affected by Differentiated Thyroid Cancer Treated with Levothyroxine Liquid Solution or Tablet Form - Carlo Cappelli; Ilenia Pirola; Elena Gandossi; Claudio Casella; Davide Lombardi; Barbara Agosti; Fiorella Marini; Andrea Delbarba; Maurizio Castellano (International Journal of Endocrinology)
Background. Recent guidelines from the American Thyroid Association (ATA) indicate that, in many patients affected by differentiated thyroid cancer (DTC), the serum TSH should be maintained between 0.1 and 0.5 mU/L. The purpose of this study was to evaluate the TSH variability of patients affected by DTC treated with liquid L-T4 formulation or in tablet form. Patients and Methods. Patients were eligible if (a) they were submitted to a total thyroidectomy and 131I remnant ablation for DTC in our institution and (b) they were classified low-risk patients according to ATA guidelines 2009. Patients were randomized (1 : 1) to receive treatment of hypothyroidism with liquid L-T4 or tablet form. The first check-up evaluation was made from 8 to 12 months after 131I remnant ablation. TSH values were established again after further 12 months. Results. A significant increase in TSH values (median) was observed in patients taking tablets [TSH (min–max): 0.28 (0.1–0.45) versus 0.34 (0.01–0.78) mIU/L, p=0.041] as compared to those taking liquid formulation [TSH (min–max): 0.28 (0.1–0.47) versus 0.30 (0.1–0.55) mIU/L, p=0.345]. Conclusions. The use of L-T4 liquid formulation, as compared to that of tablets, resulted in a significantly higher number of DTC patients maintaining TSH values in range for the ATA risk score, reducing TSH variability over the time.